PERANCANGAN BRAND CAMPAIGN SEBAGAI MEDIA PROMOSI THE PETITE PROJECT - Jovita, Jesslyn (Jurnal VICIDI, 2021)
Creativity is very important to be honed, especially during the golden age of children, which is an important moment in the growth of every child which is very dear to miss and is a period that cannot be repeated. However, most parents still do not know the importance of honing children’s creativity where they are still in the stage of growth and development, where their creativity needs to be honed as well as filling their children’s spare time while at home. The design of this final project is carried out in order to educate the market about the importance of developing or honing children’s creativity, so The Petite Project comes with a product, namely the DIY pom-pom kit which already contains tools and materials to make key chains that make it a more practical product without having to. buy tools and materials separately again. Because today many people use social media, the appropriate promotional media is social media to introduce and promote The Petite Project products in the form of a brand campaign. In collecting data for the purposes of writing a final project, the primary data and secondary data extraction method is used, where primary data is obtained through interviews with expert users and extreme users, while secondary data is obtained through literature sources from various books and journals. And the last one is done by distributing an online survey in the form of a Google Form with the aim of testing the design results that have been made to the target audience which will later be useful as criticism and suggestions for brand and product development from The Petite Project. The design results are in the form of a brand campaign to promote products as well as educate the market about the importance of honing children’s creativity. Keywords: Craft, Creativity, Product for kids, Promotion media, Social media.